Urbanization driving changes in plant species and communities – A global view - Ruas, Renata de Barros; Costa, Laís Mara Santana; Bered, Fernanda (Global ecology and conservation, 2022)
The urban landscape is becoming the environment most familiar to most of humanity, which has consequences for society, the environment, and biodiversity. Here, we present a systematic review of current research integrating several areas of urban ecology to evaluate how plants are responding to urbanization. We found that most studies were conducted in Europe and North America. The most represented biome was that of Temperate Broadleaf and Mixed Forests. The majority of studies reported negative consequences of urbanization. The Urban Drivers most commonly cited as responsible for changes in plant species and communities were Land Cover Change and Biotic Invasion. In general, urbanization reduces the richness of plant species and pollinators' availability. It also homogenizes the environment, promotes the invasion of non-native species, causes changes in phenological events, and presents difficulties for plant growth. However, some species show evidence of adaptation to these adversities through their phenotypic plasticity and the evolution of traits that make individuals resilient to the urban environment. Although it has been established that urbanization imposes novel selective pressures resulting in unique adaptations to city life, patterns of changes in biodiversity in response to urbanization can vary by region, biomes, city history, and the taxa studied. The Urban Drivers responsible for floristic responses work simultaneously by modifying the environment. Therefore, it is challenging to predict response patterns of plants under urban growth. It is necessary to outline strategies for continuous monitoring to document the progress of species in perpetuating themselves in the face of urbanization. [Display omitted] •The Urban Drivers responsible for floristic responses work simultaneously by modifying the environment.•Land Cover Change and Biotic Invasion are the most common Urban Drivers responsible for plant species and communities changes.•Most research on plants and urbanization is conducted in Temperate regions.•Plant species show resilience to urbanization through phenotypic plasticity and evolution of traits.•Patterns of changes in biodiversity in response to urbanization can vary by region, biomes, city history, and the taxa studied.